Major process equipment maintenance and repair - Bloch, Heinz P., 1933- (Practical machinery management for process plants;, 1997)
This updated edition describes preventive and predictive maintenance for major process units, such as vertical, horizontal, reciprocating and liquid-ring vacuum pumps, fans and blowers, compressors, turboexpanders and turbines.